Development of cardiorespiratory fitness standards for working memory using receiver operating curves in 15-year-old adolescents - Vinícius Muller Reis Weber; Daniel Zanardini Fernandes; Leonardo Alex Volpato; Maria Raquel de Oliveira Bueno; Marcelo Romanzini; Jose Castro-Piñero; Enio Ricardo Vaz Ronque (BMC, 2021)
Abstract Background Working memory performance is associated with better academic achievements in children and adolescents, and it is positively related to CRF. However, what level of cardiorespiratory fitness (CRF) discriminates higher working memory performance is not known. The purpose of this study was to identify CRF thresholds linked to working memory in adolescents. Methods Data of 141 adolescents (53.2 % girls) were collected (14.9 years) from a cross-sectional study during the year 2019. CRF was assessed by the 20-m shuttle run test, and maximal oxygen uptake was calculated using the Mahar´s equation. Working memory was evaluated by the Corsi blocks test and performance was classified by percentiles. Receiver operating characteristic (ROC) curve analysis was used to identify CRF thresholds. Results The ROC analysis indicated that CRF could be used to discriminate working memory in adolescents. CRF thresholds of ≥45.03 ml.kg− 1.min− 1for boys and ≥36.63 ml.kg− 1.min− 1for girls were found to be indicative of "normal" working memory performance. Conclusions CRF could discriminate low and normal working memory performance in 14-16- year-old adolescents. These thresholds could allow for earlier identification and intervention of low working memory performance using CRF.